2007
DOI: 10.1152/ajprenal.00149.2007
|View full text |Cite
|
Sign up to set email alerts
|

Insulin's impact on renal sodium transport and blood pressure in health, obesity, and diabetes

Abstract: Insulin has been shown to have antinatriuretic actions in humans and animal models. Moreover, endogenous hyperinsulinemia and insulin infusion have been correlated to increased blood pressure in some models. In this review, we present the current state of understanding with regard to the regulation of the major renal sodium transporters by insulin in the kidney. Several groups, using primarily cell culture, have demonstrated that insulin can directly increase activity of the epithelial sodium channel, the sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 167 publications
(114 reference statements)
2
95
0
1
Order By: Relevance
“…This intracellular solution helped to eliminate any inward Cl Ϫ or K ϩ current since the E Cl and E K were approximately Ϫ80 mV. In most TRCs, insulin increased inward Na ϩ currents, consistent with previous studies in other transporting epithelia that showed that the ability of insulin to enhance Na ϩ movement is through the activation of ENaC (38,44). To determine whether the insulin-enhanced responses we recorded were attributable to ENaC, we recorded insulininduced responses in the presence or absence of amiloride (30 M) and/or benzamil (10 M).…”
Section: Insulin Increases Amiloride-sensitive Na ϩ Currents In Mousesupporting
confidence: 88%
See 2 more Smart Citations
“…This intracellular solution helped to eliminate any inward Cl Ϫ or K ϩ current since the E Cl and E K were approximately Ϫ80 mV. In most TRCs, insulin increased inward Na ϩ currents, consistent with previous studies in other transporting epithelia that showed that the ability of insulin to enhance Na ϩ movement is through the activation of ENaC (38,44). To determine whether the insulin-enhanced responses we recorded were attributable to ENaC, we recorded insulininduced responses in the presence or absence of amiloride (30 M) and/or benzamil (10 M).…”
Section: Insulin Increases Amiloride-sensitive Na ϩ Currents In Mousesupporting
confidence: 88%
“…3). Similar results in kidney epithelia studies have also suggested that insulin contributes to Na ϩ movement via ENaC (43,44). Insulin-mediated Na ϩ reabsorption occurs through activation of PI3-kinase.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…90 Hyperinsulinemia is a prominent feature of insulin resistance, diabetes mellitus, and obesity. Insulin receptors are expressed in the proximal tubule, DCT, and CD.…”
Section: Hypertension In Diabetes Mellitusmentioning
confidence: 99%
“…Insulin receptors are expressed in the proximal tubule, DCT, and CD. 90 Song et al 91 showed that the rise in BP in rats on chronic insulin treatment is likely caused by enhanced sodium reabsorption by NCC and ENaC, because treatment with hydrochlorothiazide and amiloride results in increased natriuresis. Interestingly, insulin also reduces renal cortical WNK4 expression, which contributes to activation of NCC and ENaC.…”
Section: Hypertension In Diabetes Mellitusmentioning
confidence: 99%